Influência do extrato de chá verde na remodelação cardíaca induzida por administração de doxorrubicina - Modesto, Pamela Nayara [UNESP] (2015)
Doxorubicin (DOX) is a widely used drug as a chemotherapeutic agent having efficacy in the treatment of numerous cancers. However, use of this drug may provide undesirable effects such as cardiotoxicity. Various mechanisms have been proposed for doxorubicin cardiotoxicity, such as oxidative stress, inflammation and alterations in the extracellular matrix, leading to cardiac remodeling. Green tea (Camellia sinensis), the most popular drinks in the world, has demonstrated a positive relationship between regular consumption and protection against cardiovascular disease and some types of cancer. This is the antioxidant, anti-inflammatory, antiapoptotic found in catechins present in green tea. It is therefore possible that it mitigates the cardiotoxic fond of doxorubicin, slowing the process of cardiac remodeling. The aim of this study was to evaluate whether the green tea extract attenuates cardiac remodeling induced by doxorubicin, through the evaluation of biochemical variables, cell phones, and interstitial cardiac morphofunctional variables. For this, was used male Wistar rats weighing 250 to 300 grams. These animals were divided into 4 groups: CP (control) received standard chow and intraperitoneal administration of saline, CCV (control + green tea) receiving feed added green tea extract and intraperitoneal administration of saline, DX (Doxorubicin) who received standard chow and intraperitoneal administration of doxorubicin and DX-CV (doxorubicin + green tea) fed diets with added green tea extract and intraperitoneal administration of doxorubicin. The feed was supplied for 35 days and on day 33◦ doxorubicin or infusion of saline solution were carried out in the same ratio (20 mg / kg single dose) and the animals were euthanized 48 hours after drug injection. The rats were subjected to the echocardiography before and 48 hours after injection of doxorubicin. Was conducted evaluation of oxidative stress by spectrophotometry ...